The Effect of Information Quality and Brand Image on Shopee Food Repurchase Interest Mediated by Customer Trust - Andykiawan Ega Dangga; Ida Bagus Nyoman Udayana; Putri Dwi Cahyani (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of this study is to examine how consumer confidence mediates the relationship between information quality and brand image and repurchase interest in Shopee food. Specifically, the study will look at Yogyakarta-based Shopee e-commerce users.In order to gather data for this study, a descriptive-quantitative research method was employed. A sample of 104 people was required, and surveys were completed online using Google Forms and distributed via Facebook, Instagram, and Whatsapp. The data was then processed using SPSS 25 software to determine the findings. After analysis, it was discovered that repurchase interest (Y) is influenced by information quality (X1), brand image (X2), and consumer confidence (Z). Information quality (X1) and brand image (X2) are influenced by consumer trust (Z), and consumer trust variable is able to mediate the relationship between information quality, brand image, and consumer trust